Thermal decomposition of nanostructured Aluminum Titanate in an active Al matrix: A novel approach to fabrication of in situ Al/Al2O3–Al3Ti composites. (25th December 2015) - Azarniya, Abolfazl; Hosseini, Hamid Reza Madaah; Jafari, Mohadese; Bagheri, Niloofar
Abstract: The thermal decomposition of Aluminum Titanate in exposure to pure Aluminum was examined both in powder and in bulk form. Optical microscopy, FE-SEM, XRD, DSC and TGA examinations were conducted to take the possible chemical reactions between Aluminum Titanate and Al into consideration. It was found that as Aluminum Titanate particles are exposed to Al matrix, the thermal stability of Aluminum Titanate is degraded and its decomposition temperature is reduced from 850 °C to 550 °C. Also, the chemical reactions between Aluminum Titanate and Al start along the interfaces, and the reaction products, i.e. Al3 Ti, Al2 O3, TiO2 and O2 gas are left there. A mechanism was suggested to describe the Al/Al2 TiO5 interactions in the interfaces. It was shown that the reaction products of nanostructured Al2 TiO5 particle decomposition can be used as a source for producing in situ Al/Al3 Ti and Al2 O3 reinforced metal matrix composites through the solid-state powder metallurgy route. Finally, a uniformly dense microstructure including submicron Al2 O3 and nanosized Al3 Ti reinforcements was obtained. Graphical abstract: Highlights: We focused on thermal decomposition of Al2 TiO5 in exposure to active Al matrix. It was found that Al matrix can reduce the degradation temperature up to 550 °C. A mechanism and a model was suggested to describe the reactions between AT and Al. AT can be used as a chemical source for producing in situ Al3 Ti and Al2 O3 reinforcements.